Urgensi Pembentukan Sopan Santun Anak Melalui Model Pembelajaran Islamic Parenting di TK Islam Pancor Kopong - arfini, baiq desy; Hamdan, Hamdan; Junaidi, M; Iswandi, Lalu (FAKULTAS TARBIYAH, 2024)
Islamic parenting is an Islamic parenting style. One of the Islamic principles that will be implemented at the Pancor Kopong Islamic Kindergarten is Manners. The phenomenon of students who are less polite towards their teachers and parents, and less polite towards their peers. So that children in the school environment do not have a polite attitude towards their school friends, including what happens to children around Pancor Kopong Hamlet, Pringgasela Village. It is interesting to study such issues in more depth, which is what underlies this research with the title